Performance Benchmarking Methodologies for Real-Time Integration Middleware Platforms - Neela, Suman (American International Journal of Computer Science and Technology, 2023)
Real-time integration middleware sits at the core of how modern enterprises move data, trigger actions, and keep distributed systems in sync. Platforms like Apache Kafka, RabbitMQ, IBM MQ, and Apache Pulsar carry the weight of mission-critical operations—from payment processing and supply chain coordination to IoT data collection and distributed analytics. Yet, despite how much it depends on them, the methods used to benchmark their performance are still surprisingly immature. Most current ways of testing these systems—like checking the infrastructure, running application load tests, or assessments done by vendors—fail to capture the important behaviors that really affect their performance in real situations: how well they handle sudden spikes in traffic, how they deal with pressure, and if keeping messages safe slows things down too much. This article covers the theoretical basis for middleware performance evaluation, maps out where current practice falls short, and offers a detailed look at the Middleware-Aware Performance Benchmarking Framework (MAP-Bench). MAP-Bench combines a set of standard measurements, models for business workloads, tests for handling faults, and a more advanced way to evaluate architecture into one complete method. The practical value extends to platform selection, capacity planning, SLA design, and performance tuning. The goal is to move middleware benchmarking away from narrow load testing and toward something that actually reflects how these systems perform when it counts.